Development of an E-Book Based Digital Learning Medium for Records Management among Eleventh Grade Office Management Students at SMKN 12 Jakarta - Shalsa Nurliana; Darma Rika Swaramarinda; Ferry Setyadi Atmadja (The Future of Education Journal, 2026)
This study aimed to develop digital learning media in the form of an e-book for the Archival Management subject for Grade XI Office Management students at SMKN 12 Jakarta. The study employed the Research and Development (R&D) method using the ADDIE model. The product developed was an interactive e-book containing Archival Management materials, images, instructional videos, and practice exercises that can be accessed digitally.The results of the study showed that the developed e-book was categorized as highly feasible, based on the validation results of media experts with a score of 92.5%, instructional design experts with a score of 92.5%, and subject matter experts with a score of 97%. Furthermore, the effectiveness test results indicated an improvement in students’ learning outcomes after using the e-book in the learning process, as evidenced by an N-Gain score of 0.8684. Therefore, the digital learning media in the form of an e-book developed in this study was considered feasible and effective for use as a learning medium in the Archival Management subject.